Characteristics of Zonda Wind in South American Andes - Loredo Souza, Acir M. (2017)
This paper discusses some features and conditions that characterize the Zonda wind, focusing particularly on the implications for wind engineering applications. This kind of wind, typical of mountainous regions, is far from being adequately characterized for computational simulations andproper modeling in experimental facilities such as boundary layer wind tunnels. The objective of this article is to report the research works that are being developed on this kind of wind, describing the main obtained results, and also to establish some general guidelines for the proper analysis of the Zonda in the wind engineering context. A classification for the Zonda wind is indicated and different cases of structural and environmental effects are described. Available meteorological data is analyzed from the wind engineering point of view to obtain the Zonda wind gust factors, as well as basic wind speeds relevant for structural design. Some considerations and possible directions for the Zonda wind-tunnel and computational modeling are provided. Gust factor values larger than those used for open terrain were obtained, nevertheless, the basic wind speed values obtained are similar to values presented by the Argentinian Wind Code for three-second gust, principally at Mendoza airport.